Power Balancing Control for Grid Energy Storage System in Photovoltaic Applications—Real Time Digital Simulation Implementation - Sridhar Vavilapalli; Sanjeevikumar Padmanaban; Umashankar Subramaniam; Lucian Mihet-Popa (Energies, 2017)
A grid energy storage system for photo voltaic (PV) applications contains three different power sources i.e., PV array, battery storage system and the grid. It is advisable to isolate these three different sources to ensure the equipment safety. The configuration proposed in this paper provides complete isolation between the three sources. A Power Balancing Control (PBC) method for this configuration is proposed to operate the system in three different modes of operation. Control of a dual active bridge (DAB)-based battery charger which provides a galvanic isolation between batteries and other sources is explained briefly. Various modes of operation of a grid energy storage system are also presented in this paper. Hardware-In-the-Loop (HIL) simulation is carried out to check the performance of the system and the PBC algorithm. A power circuit (comprised of the inverter, dual active bridge based battery charger, grid, PV cell, batteries, contactors, and switches) is simulated and the controller hardware and user interface panel are connected as HIL with the simulated power circuit through Real Time Digital Simulator (RTDS). HIL simulation results are presented to explain the control operation, steady-state performance in different modes of operation and the dynamic response of the system.